Educating the society towards a higher level of technological awareness - Mohd Ali, Borhanuddin; Mokhtar, Adznir; Malek, Abdul Fatah (1990)
As the level of prosperity in the society grows so will the level of consumerism. The public are constantly fed with multifarious products which becomes more sophisticated by the day. Thus the public will have to be educated on the whats and the hows of the goodies so that they are aware of the capacity and limitations of the products. The rural folk who are generally less sophisticated should also be given a certain level of technological understanding to keep them abreast with the modernisation process and benefit from it. A lot of the agricultural process can still be modernised through the use of machineries, irrigation, etc. Infrastructures such as roads, water and electricity supply, and telephone, can be made available to the people far away from the cities. Agency workers that handle the development of the rural areas should be given more education on engineering and technological knowhow so as to be able to impart the knowledge to the people directly. This paper will discuss the role that engineers and the engineering educators should play in upgrading the level of technological and engineering knowledge on the society.